Proposal and Model for Designing a Cybrary - With Reference to Fr. Moseslibrary, Rajagiri College of Social Sciences, Kerala - Tripathi, Richa; Vijayan, Vijesh (Journal of Information and Knowledge, 2019)
Subject gateways are becoming one of the most commonly used media for effective and efficient delivery of information as it not only offers information about library resources and services, but also provides all the open access resources such as electronic books, electronic journals, online databases, online dictionary, encyclopedia, bibliography, software, etc. The Cybrary – Open Access Subject gateway proposal brings together all open access e-resources at one place so that the students, research scholars and faculty members may make optimum use of them. The building of a strong subject gateway for Library is needed in the present scenario as a tool which is useful for all users.